Beta molecular sieve, preparation method thereof and deoxidation catalyst
By controlling the amount of water and alkalinity and using tetraethylammonium hydroxide as a template agent, the synthesis time of Beta molecular sieves is shortened, solving the problems of high water consumption and energy consumption, and obtaining an efficient and low-energy-consumption method for synthesizing Beta molecular sieves.
Patent Information
- Application Number
- CN202410430040.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-10
- Publication Date
- 2025-10-17
AI Technical Summary
Existing technologies for molecular sieve synthesis consume large amounts of water and generate wastewater. Furthermore, solvent-free synthesis methods are time-consuming and energy-intensive, resulting in low efficiency.
By reducing the amount of water used and controlling the alkalinity of the raw material mixture and the concentration of the template agent, the crystallization nucleation rate and crystal growth rate of Beta molecular sieve are improved, and the preparation time is shortened. Tetraethylammonium hydroxide is used as a template agent, and the silicon-aluminum molar ratio is controlled within a specific range to carry out low-temperature short-time crystallization.
This method achieves reduced energy consumption, reduced wastewater discharge, improved molecular sieve preparation efficiency, and yields highly crystalline Beta molecular sieves with open pore structures.
Smart Images

Figure CN120793957A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of molecular sieve synthesis and deoxygenation of oxygen-containing organic gas, and in particular to a Beta molecular sieve, a preparation method thereof and a deoxygenation catalyst. BACKGROUND
[0002] Molecular sieves are a kind of common porous materials, which have important applications in petroleum and chemical industry, fine chemical industry and other fields due to their unique pore structure and high stability. Beta molecular sieve is a type of molecular sieve with BEA topology structure, which has three-dimensional 12-membered ring open channels. The unique structure endows it with wide applications, such as catalytic cracking, hydroisomerization and alkylation processes in the field of oil refining. In addition, it is found that molecular sieves can be used for catalytic deoxygenation treatment of oxygen-containing organic tail gas by loading metal active species.
[0003] The mainstream synthesis method of molecular sieves in the current industry is hydrothermal synthesis method, which is relatively mature. Wang Luya of Huami Technology Co., Ltd. disclosed a synthesis method of Beta molecular sieve (CN 104229821B). After the aluminum source solution is heat-activated for >12 h, it is mixed with a silicon source, and then crystallized at 120-180℃ for 24-48 h to obtain a Beta molecular sieve product with high crystallinity. Lan Chunfeng et al. of Shanghai Zhuoyue Chemical Technology Co., Ltd. invented a method for synthesizing Beta molecular sieve (CN 103787355B). By using a species containing fluorine element to treat the Beta molecular sieve seed to generate active species with structure guiding effect, and adding it into the molecular sieve synthesis gel, a Beta molecular sieve product with a wide distribution of silicon-aluminum ratio and high cleanliness can be obtained. Zhao Yan et al. of Chemical Engineering and Technology University developed a phase transfer method to synthesize Beta molecular sieve (Zhao Yan et al., Chemical Reaction Engineering and Technology, 2021, 37, 4, 296-304). Toluene and water were used as solvents respectively to crystallize the Beta molecular sieve species at 140℃ for 3 days. The product obtained has more medium-strong B acid sites compared with the product obtained by the conventional method, and obtains more suitable reaction performance in tetralin hydrocracking reaction.
[0004] Although the above methods and similar methods in the prior art can obtain completely crystallized molecular sieve products, a large amount of water resources are consumed and high-salt wastewater is generated, which does not meet the current requirements of green chemistry. The existing solvent-free synthesis method of Beta molecular sieve often needs >24 h of crystallization time under high temperature conditions, which leads to low efficiency of molecular sieve preparation, and the long-time maintenance of high temperature increases the energy consumption. Reducing the synthesis cost of Beta molecular sieve and the consumption of resources and energy is always the common goal pursued by researchers in the field of molecular sieve synthesis. SUMMARY
[0005] The present application aims to overcome the problems of the prior art, such as the need for a large amount of water in the synthesis of molecular sieves, thus producing a large amount of wastewater, and the long crystallization time of the solvent-free synthesis of Beta molecular sieves, thus resulting in low efficiency and high energy consumption, and provides a Beta molecular sieve and a preparation method thereof and a deoxygenation catalyst, which can improve the nucleation rate and crystal growth rate of the molecular sieve by reducing the amount of water and reasonably controlling the alkalinity of the raw material mixture, thus shortening the preparation time of the molecular sieve and achieving the purpose of reducing energy consumption, while reducing the discharge amount of wastewater.
[0006] To achieve the above-mentioned purpose, the present application provides a Beta molecular sieve in a first aspect, wherein the crystal size of the Beta molecular sieve is 10-550nm, the specific surface area is 350-450m 2 / g, and the molar ratio of silicon to aluminum is 10-80:1.
[0007] Preferably, in the Beta molecular sieve, the molar ratio of silicon to aluminum is 10-60:1.
[0008] The present application provides a method for preparing a Beta molecular sieve in a second aspect, which comprises the following steps:
[0009] (1) mixing a silicon source, an aluminum source, a template agent, a base and water to obtain a raw material mixture;
[0010] (2) placing the raw material mixture for 0.5-3h, then crystallizing for 30-180min, and calcining;
[0011] Preferably, in step (1), the molar ratio of the amounts of the silicon source, the aluminum source, the template agent, the base and water is 1-250:0.05-18:0.3-42:1:5-625, the silicon source is calculated as SiO2, and the aluminum source is calculated as Al2O3.
[0012] Preferably, in step (1), the molar ratio of the amounts of the silicon source, the aluminum source, the template agent, the base and water is 1-250:0.05-18:0.3-42:1:5-625, the silicon source is calculated as SiO2, and the aluminum source is calculated as Al2O3.
[0013] Preferably, in step (2), the crystallization time is 40-150min.
[0014] Preferably, in step (2), the raw material mixture is placed for 1-2h.
[0015] Preferably, in step (1), the aluminum source is selected from one or two or more of sodium metaaluminate, aluminum hydroxide and pseudo-boehmite.
[0016] Preferably, in step (1), the silicon source is selected from one or two or more of silica gel, attapulgite and white carbon black.
[0017] Preferably, in step (1), the base is selected from one or more of sodium hydroxide, potassium hydroxide and sodium carbonate.
[0018] Preferably, in step (2), the temperature of the crystallization is 150-200°C, preferably 160-190°C.
[0019] Preferably, in step (2), the conditions of the calcination include that the temperature of the calcination is 500-600°C and the time of the calcination is 4-6h.
[0020] The third aspect of the present application provides a Beta zeolite prepared by the method as described above.
[0021] The fourth aspect of the present application provides a deoxidation catalyst, wherein the deoxidation catalyst has the Beta zeolite as described above as a carrier.
[0022] Preferably, the active component of the deoxidation catalyst is one or more of platinum oxide, palladium oxide, silver oxide or gold oxide.
[0023] Preferably, the content of the carrier is 97-99.9wt% and the content of the active component is 0.1-3wt% based on the total weight of the deoxidation catalyst.
[0024] Compared with the prior art, the present application has at least the following advantages:
[0025] In the process of preparing the Beta zeolite, the present application increases the concentration of the raw material mixture by reducing the amount of water, thereby increasing the nucleation rate of the Beta zeolite in the crystallization; at the same time of reducing the amount of water, the present application controls the amount of base to control the alkalinity of the raw material mixture within an appropriate range and controls the amount of the specific template to increase the concentration of the template within an appropriate range, thereby increasing the crystal growth rate; thus, the present application shortens the preparation time of the Beta zeolite by increasing the nucleation rate and the crystal growth rate in the crystallization, thereby achieving the purpose of reducing the energy consumption.
[0026] In addition, since the method reduces the amount of water, the present application can save water resources and reduce the amount of wastewater. BRIEF DESCRIPTION OF DRAWINGS
[0027] Figure 1 is the XRD spectrum of the Beta zeolite prepared in Example 1;
[0028] Figure 2 is the SEM picture of the Beta zeolite prepared in Example 1. DETAILED DESCRIPTION
[0029] The specific embodiments of the present application will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are merely illustrative and explanatory and are not intended to limit the present application.
[0030] The endpoints of the ranges and any values disclosed herein are not limited to the precise values stated. The endpoints of the ranges and any values are provided as approximate descriptions and are understood to include values near the recited ones within the range, unless otherwise specificly stated. For ranges with endpoints, the endpoints are included within the range. For ranges without endpoints, the range is understood to include any value within the range.
[0031] The first aspect of the present application provides a Beta zeolite, which has high crystallinity, a crystal size of 10-550nm, a specific surface area of 350-450m 2 / g; and a silicon-aluminum molar ratio of 10-80:1.
[0032] The Beta zeolite provided by the present application has an open structure, and the pores are not blocked, being smooth and open.
[0033] In some preferred embodiments, the silicon-aluminum molar ratio of the Beta zeolite provided by the present application is 10-60:1.
[0034] The second aspect of the present application provides a method for preparing a Beta zeolite, which comprises the following steps:
[0035] (1) mixing a silicon source, an aluminum source, a template agent, a base and water to obtain a raw material mixture;
[0036] (2) placing the raw material mixture for 0.5-3h, then crystallizing for 30-180min, and calcining.
[0037] In the method described in the present application, a specific template agent needs to be used to prepare the Beta zeolite with the aforementioned characteristics.
[0038] In the present application, the template agent is tetraethylammonium hydroxide.
[0039] In specific embodiments, the molar ratio of the amounts of the silicon source, the aluminum source, the template agent, the base and water is 1-250:0.05-18:0.3-42:1:5-625, the silicon source being calculated as SiO2, and the aluminum source being calculated as Al2O3. Controlling the molar ratio of the components of the present application within the aforementioned ranges can prepare a Beta zeolite with high crystallinity, appropriate crystal size, specific surface area and silicon-aluminum molar ratio.
[0040] In the method, by reasonably controlling the ratio of the raw materials, the nucleation rate and the crystal growth rate of the Beta molecular sieve are improved, so that the preparation time of the Beta molecular sieve is shortened, the energy consumption is reduced, the water consumption is reduced, the water resource is saved, and the wastewater discharge is reduced.
[0041] Specifically, on the one hand, the concentration of the raw material mixture is increased by reducing the water consumption, so that the nucleation rate of the Beta molecular sieve is increased; on the other hand, by controlling the amount of the alkali and the amount of the template agent, the alkalinity of the raw material mixture is controlled within a proper range and the concentration of the template agent is increased within a proper range, so that the crystal growth rate is increased.
[0042] In addition, the water consumption is small, the raw material mixture is a gel, and by controlling the ratio of the raw materials within the range, the gel concentration of the Beta molecular sieve is maximized, and the water-silicon ratio of the crystal growth of the Beta molecular sieve is ensured to be suitable, so that the gel ratio is within the synthesis phase region, and the Beta molecular sieve with complete crystallization can be prepared. Further, only a specific template agent can be used in the method to prepare the Beta molecular sieve with the characteristics described above.
[0043] In some preferred embodiments, in step (1), the molar amount of the silicon source (calculated as SiO2), the aluminum source (calculated as Al2O3), the template agent, the alkali, and the water is 1.5-200:0.15-15:0.4-40:1:7-623.
[0044] In the present application, the silicon source can be a conventional choice in the art.
[0045] In the present application, the silicon source can be a conventional choice in the art.
[0046] Specifically, in step (1), the silicon source can be selected from one or more of silica gel, attapulgite, and white carbon black.
[0047] In the present application, the silica gel is inorganic silica gel with a chemical formula of SiO2, which is purchased from Aldrich Reagent; the attapulgite is magnesium aluminum silicate with a chemical formula of 603SiO2.Al2O3.3MgO, which is purchased from National Pharmaceutical Group; and the white carbon black has a chemical formula of SiO2, which is purchased from Aldrich Reagent.
[0048] In the present application, the alkali can be a conventional choice in the art.
[0049] Specifically, in step (1), the base is selected from one or more of sodium hydroxide, potassium hydroxide and sodium carbonate.
[0050] In preferred embodiments, before mixing the raw materials, the silicon source, the aluminum source, the template agent and the like can be ground uniformly.
[0051] In step (1), the mixing of the silicon source, the aluminum source, the template agent, the base and water is not particularly limited in order, as long as the mixture is uniform.
[0052] In preferred embodiments, the template agent and water are mixed first to obtain a template agent solution, then the silicon source and the aluminum source are mixed, and then the base is added for mixing.
[0053] In the present application, the crystallization time of the Beta molecular sieve is relatively short. Preferably, in step (2), the crystallization time is 40-150 min, such as 40 min, 50 min, 55 min, 60 min, 70 min, 75 min, 80 min, 85 min, 90 min, 100 min, 110 min, 120 min, 130 min, 140 min or 150 min.
[0054] In the present application, before the raw material mixture is crystallized, the raw material mixture is allowed to stand for a specific period of time, which can allow the mixture to age and pre-react sufficiently.
[0055] In some preferred embodiments, in step (2), the raw material mixture is allowed to stand for 1-2 h.
[0056] In the method of the present application, specifically, the crystallization can be carried out in a crystallization reactor commonly used in the art.
[0057] In some embodiments, in step (2), the crystallization temperature is 150-200°C, preferably 160-200°C, such as 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C or 200°C.
[0058] In specific embodiments, after the crystallization is completed, the crystallized product is washed with water, centrifuged, dried, and then calcined.
[0059] In some embodiments, in step (2), the calcination conditions include a calcination temperature of 500-600°C and a calcination time of 4-6 h.
[0060] In the present application, after calcination, the organic molecules such as template agent do not block the channels of the molecular sieve, thus the Beta molecular sieve obtained by the method of the present application has an open structure, i.e. the channels of the Beta molecular sieve are not blocked, and are smooth and open.
[0061] The third aspect of the present application provides a Beta molecular sieve prepared by the method described above.
[0062] In a preferred embodiment, the Beta molecular sieve has high crystallinity, the crystal size is 50-300 nm, the specific surface area is 350-450 m 2 / g; and the molar ratio of silicon to aluminum is 10-80:1.
[0063] In a more preferred embodiment, the molar ratio of silicon to aluminum of the Beta molecular sieve provided by the present application is 10-60:1.
[0064] The fourth aspect of the present application provides a deoxidation catalyst, wherein the Beta molecular sieve described above is used as a carrier.
[0065] In some preferred embodiments, the active component of the deoxidation catalyst is one or two or more of platinum oxide, palladium oxide, silver oxide or gold oxide.
[0066] In a more preferred embodiment, the content of the carrier is 97-99.9% by weight, and the content of the active component is 0.1-3% by weight, based on the total weight of the deoxidation catalyst.
[0067] The present application will be described in detail below by way of examples, but the scope of protection of the present application is not limited thereto.
[0068] In the following examples and comparative examples, the reagents used are all common commercially available products unless otherwise specified.
[0069] In the following examples and comparative examples:
[0070] The pseudoboehmite is Al2O3 2H2O;
[0071] The silica gel is inorganic silica gel with the chemical formula of SiO2, which is purchased from Aldrich Reagent;
[0072] The attapulgite is a magnesium aluminum silicate with the chemical formula of 603SiO2.Al2O3.3MgO, which is purchased from National Pharmaceutical Group;
[0073] The white carbon black has the chemical formula of SiO2, which is purchased from Aldrich Reagent.
[0074] Examples 1-10 are used to illustrate the preparation process of the Beta molecular sieve.
[0075] Example 1
[0076] The method for preparing the Beta molecular sieve comprises the following steps:
[0077] After 1.5 g of silica gel, 0.051 g of sodium metaaluminate and 2.0 g of a tetraethylammonium hydroxide aqueous solution (25 wt% in concentration) are uniformly mixed, 0.08 g of sodium hydroxide is added, and the molar ratio of the amounts of the silica gel (calculated as SiO2), the sodium metaaluminate (calculated as Al2O3), the tetraethylammonium hydroxide, the sodium hydroxide and water is 12.5:0.156:1.7:1:41.67, the above raw materials are uniformly mixed, and then are left to stand for 2 h, and then are transferred to a stainless steel tube with a polytetrafluoroethylene lining, and are crystallized at 180°C for 55 min. After the crystallization is completed, the obtained product is subjected to deionized water washing and centrifugal separation, is dried at 50°C after the water is removed, and then is calcined at 550°C for 5 h.
[0078] The XRD spectrum and the SEM image of the product prepared in this example are shown in Figure 1 and Figure 2 It can be seen from Figure 1 that the spectrum gives diffraction peaks belonging to the MFI topology, and the clear peak intensity indicates that the obtained molecular sieve material has high crystallinity; it can be seen from Figure 2 that the grain morphology of the obtained molecular sieve is irregular, and the size is 30-100 nm.
[0079] Example 2
[0080] The method for preparing the Beta molecular sieve comprises the following steps:
[0081] After 1.5 g of attapulgite, 0.105 g of sodium metaaluminate and 1.5 g of a tetraethylammonium hydroxide aqueous solution (35 wt% in concentration) are uniformly mixed, 0.005 g of sodium hydroxide is added, and the molar ratio of the amounts of the attapulgite (calculated as SiO2), the sodium metaaluminate (calculated as Al2O3), the tetraethylammonium hydroxide, the sodium hydroxide and water is 20:5.12:28.52:1:433.33, the above raw materials are uniformly mixed, and then are left to stand for 1 h, and then are transferred to a stainless steel tube with a polytetrafluoroethylene lining, and are crystallized at 170°C for 50 min. After the crystallization is completed, the obtained product is subjected to deionized water washing and centrifugal separation, is dried at 100°C after the water is removed, and then is calcined at 550°C for 5 h.
[0082] The XRD spectrum result shows that the Beta molecular sieve prepared in this example has high crystallinity.
[0083] Example 3
[0084] The method for preparing the Beta molecular sieve comprises the following steps:
[0085] After 2.0 g of white carbon black, 0.150 g of sodium metaaluminate and 1.0 g of tetraethylammonium hydroxide aqueous solution (concentration of 35% by weight) were uniformly mixed, 0.100 g of sodium hydroxide was added, and the molar ratio of the amounts of white carbon black (calculated as Si02), sodium metaaluminate (calculated as Al203), tetraethylammonium hydroxide, sodium hydroxide and water was 13.33:0.37:0.95:1:14.44, the above raw materials were uniformly mixed, and then were placed for 1.5 h, and then were transferred to a stainless steel tube with a polytetrafluoroethylene liner, and were crystallized at 180°C for 40 min. After the crystallization was completed, the obtained product was washed with deionized water and was centrifuged, was dried at 100°C after the water was removed, and then was calcined at 550°C for 5 hours to obtain a Beta zeolite.
[0086] The XRD spectrum results show that the Beta zeolite prepared in this example has high crystallinity.
[0087] Example 4
[0088] The method for preparing the Beta zeolite comprises the following steps:
[0089] After 1.5 g of silica gel, 0.15 g of sodium metaaluminate and 2.0 g of tetraethylammonium hydroxide (35% by weight aqueous solution) were uniformly mixed, 0.005 g of sodium hydroxide was added, and the molar ratio of the amounts of silica gel (calculated as Si02), sodium metaaluminate, tetraethylammonium hydroxide, sodium hydroxide and water was 20:0.73:3.8:1:57.78, the above raw materials were uniformly mixed, and then were placed for 2.5 h, and then were transferred to a stainless steel tube with a polytetrafluoroethylene liner, and were crystallized at 160°C for 150 min. After the crystallization was completed, the obtained product was washed with deionized water and was centrifuged, was dried at 100°C after the water was removed, and then was calcined at 550°C for 5 hours.
[0090] The XRD spectrum results show that the Beta zeolite prepared in this example has high crystallinity.
[0091] Example 5
[0092] The method for preparing the Beta zeolite comprises the following steps:
[0093] After 1.5 g of silica gel, 0.076 g of sodium metaaluminate and 2.0 g of tetraethylammonium hydroxide aqueous solution (concentration of 25% by weight) were uniformly mixed, 0.08 g of sodium hydroxide was added, and the molar ratio of the amounts of the silica gel (calculated as Si02), sodium metaaluminate (calculated as Al203), tetraethylammonium hydroxide, sodium hydroxide and water was 12.5:0.23:1.7:1:41.67. After the above raw materials were uniformly mixed, standing for 2 h, the mixture was transferred to a stainless steel tube equipped with a polytetrafluoroethylene liner, and crystallization was performed at 180°C for 55 min. After the crystallization was completed, the obtained product was washed with deionized water and subjected to centrifugal separation, and after the water was removed, the product was dried at 50°C and then calcined at 550°C for 5 h.
[0094] The XRD spectrum results show that the Beta zeolite prepared in this example has high crystallinity.
[0095] Example 6
[0096] The method for preparing the Beta zeolite comprises the following steps:
[0097] After 1.5 g of silica gel, 0.049 g of aluminum hydroxide and 1.3 g of tetraethylammonium hydroxide aqueous solution (concentration of 35% by weight) were uniformly mixed, 0.08 g of sodium hydroxide was added, and the molar ratio of the amounts of the silica gel (calculated as Si02), aluminum hydroxide (calculated as Al203), tetraethylammonium hydroxide, sodium hydroxide and water was 12.50:0.31:1.54:1:23.47. After the above raw materials were uniformly mixed, standing for 2 h, the mixture was transferred to a stainless steel tube equipped with a polytetrafluoroethylene liner, and crystallization was performed at 180°C for 50 min. After the crystallization was completed, the obtained product was washed with deionized water and subjected to centrifugal separation, and after the water was removed, the product was dried at 50°C and then calcined at 550°C for 5 h.
[0098] The XRD spectrum results show that the Beta zeolite prepared in this example has high crystallinity.
[0099] Example 7
[0100] The method for preparing the Beta zeolite comprises the following steps:
[0101] The method of Example 1 was implemented, except that the aluminum source was replaced by pseudo-boehmite instead of sodium metaaluminate.
[0102] The specific preparation process is as follows:
[0103] After 1.5 g of silica gel, 0.051 g of pseudoboehmite, and 2.0 g of a tetraethylammonium hydroxide aqueous solution (concentration: 25% by weight) were uniformly mixed, 0.08 g of sodium hydroxide was added, and the raw materials were mixed such that the molar ratio of silica gel (in terms of Si02), pseudoboehmite (in terms of Al203), tetraethylammonium hydroxide, sodium hydroxide, and water was 12.50:0.18:1.70:1:41.67. After the raw materials were uniformly mixed and allowed to stand for 2 hours, the mixture was transferred to a stainless steel tube equipped with a polytetrafluoroethylene liner, and crystallization was performed at 180°C for 65 minutes. After the completion of the crystallization, the obtained product was washed with deionized water and subjected to centrifugal separation, and after the removal of water, the product was dried at 50°C and then calcined at 550°C for 5 hours.
[0104] The XRD pattern results show that the Beta zeolite prepared in this example has high crystallinity.
[0105] Example 8
[0106] The method for preparing the Beta zeolite includes the following steps:
[0107] After 2.5 g of silica gel, 0.060 g of sodium metaaluminate, and 1.0 g of a tetraethylammonium hydroxide aqueous solution (concentration: 35% by weight) were uniformly mixed, 0.2 g of sodium hydroxide was added, and the raw materials were mixed such that the molar ratio of silica gel (in terms of Si02), sodium metaaluminate (in terms of Al203), tetraethylammonium hydroxide, sodium hydroxide, and water was 8.33:0.073:0.48:1:7.22. After the raw materials were uniformly mixed and allowed to stand for 2 hours, the mixture was transferred to a stainless steel tube equipped with a polytetrafluoroethylene liner, and crystallization was performed at 190°C for 48 minutes. After the completion of the crystallization, the obtained product was washed with deionized water and subjected to centrifugal separation, and after the removal of water, the product was dried at 50°C and then calcined at 550°C for 5 hours.
[0108] The XRD pattern results show that the Beta zeolite prepared in this example has high crystallinity.
[0109] Example 9
[0110] The method for preparing the Beta zeolite includes the following steps:
[0111] After 1.5 g of silica gel, 0.060 g of sodium metaaluminate and 3.0 g of a tetraethylammonium hydroxide aqueous solution (25% by weight) were uniformly mixed, 0.2 g of sodium hydroxide was added, and the molar ratio of the amounts of the silica gel (calculated as SiO2), sodium metaaluminate (calculated as Al2O3), tetraethylammonium hydroxide, sodium hydroxide and water was 5.00:0.73:1.02:1:25. After the above raw materials were uniformly mixed, they were allowed to stand for 2 h, and then transferred to a stainless steel tube equipped with a polytetrafluoroethylene liner, and crystallized at 160°C for 180 min. After the crystallization was completed, the resulting product was washed with deionized water and subjected to centrifugal separation, and after the water was removed, the product was dried at 50°C, and then calcined at 550°C for 5 h.
[0112] The XRD spectrum results show that the Beta zeolite prepared in this example has high crystallinity.
[0113] Comparative Example 1
[0114] The method of Example 1 was followed, except that the template was changed from tetraethylammonium hydroxide to tetramethylammonium hydroxide.
[0115] The specific preparation process was as follows:
[0116] After 1.5 g of silica gel, 0.051 g of sodium metaaluminate and 2.0 g of a tetramethylammonium hydroxide aqueous solution (25% by weight) were uniformly mixed, 0.08 g of sodium hydroxide was added, and the weight ratio of the amounts of the silica gel (calculated as SiO2), sodium metaaluminate (calculated as Al2O3), tetramethylammonium hydroxide, sodium hydroxide and water was 12.5:0.156:2.75:1:41.67. After the above raw materials were uniformly mixed, they were allowed to stand for 2 h, and then transferred to a stainless steel tube equipped with a polytetrafluoroethylene liner, and crystallized at 180°C for 55 min. After the crystallization was completed, the resulting product was washed with deionized water and subjected to centrifugal separation, and after the water was removed, the product was dried at 50°C, and then calcined at 550°C for 5 h to obtain a treated product.
[0117] The XRD spectrum shows that the material prepared in this comparative example is an amorphous structure, and it can be seen that, in the present application, if tetraethylammonium hydroxide is not used as a template, the Beta zeolite with high crystallinity described in the present application cannot be obtained.
[0118] Test Example 1
[0119] The silicon-aluminum molar ratios of the products obtained in Examples 1-9 and Comparative Example 1 were tested and calculated by inductively coupled plasma atomic emission spectrometry, and the results are shown in Table 1.
[0120] Table 1
[0121] silica to alumina molar ratio (SiO2 / Al2O3) Example 1 78 Example 2 41 Example 3 36.5 Example 4 26 Example 5 52 Example 6 81 Example 7 79 Example 8 110 Example 9 69 Comparative Example 1 78
[0122] Test Example 2
[0123] The crystal size of the product obtained in Test Examples 1-9 and Comparative Example 1 was tested, and the results are shown in Table 2.
[0124] Table 2
[0125]
[0126]
[0127] Application Example
[0128] The application example is used to illustrate the preparation process of the deoxidation catalyst.
[0129] The preparation method is as follows: a palladium precursor, palladium nitrate, is loaded on the Beta molecular sieve prepared in Example 1 by an equal-volume impregnation method, and after impregnation is completed, the material is calcined at 500 DEG C for 4 h to obtain the deoxidation catalyst.
[0130] After testing, the carrier of the deoxidation catalyst prepared in the application example is the Beta molecular sieve, the active component is PdO, the content of the carrier is 99.7 wt%, and the content of the active component is 0.3 wt%.
[0131] Test Example 3
[0132] The performance of the deoxidation catalyst prepared in Test Example 11 is tested.
[0133] The testing process is as follows: propylene gas containing 3 vol% of oxygen is used as the test gas, the pressure is 0.3 MPaG, and a fixed bed reactor is used to evaluate the deoxidation performance of the catalyst.
[0134] The running results show that the deoxidation rate is >97% at a reaction temperature of 280 DEG C, and the performance of the catalyst does not change significantly after stable operation for 1000 h.
[0135] It can be seen that the Beta molecular sieve prepared by the application is used as the carrier to prepare the deoxidation catalyst, the deoxidation rate is high, and the performance is stable.
[0136] The above describes the preferred embodiments of the application in detail, but the application is not limited thereto. Within the technical concept of the application, various simple modifications can be made to the technical solutions of the application, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be considered as disclosed by the application and fall within the protection scope of the application.
Claims
1. A Beta molecular sieve, characterized in that The crystal size of the Beta molecular sieve is 10-550nm and the specific surface area is 350-450m 2 / g; the silicon-aluminum molar ratio is 10-80:
1.
2. The Beta molecular sieve according to claim 1, characterized in that In the Beta molecular sieve, the molar ratio of silicon to aluminum is 10-60:
1.
3. A method for preparing Beta molecular sieve, characterized in that: The method comprises the following steps: (1) mixing a silicon source, an aluminum source, a template, an alkali, and water to obtain a raw material mixture; (2) allowing the raw material mixture to stand for 0.5-3 hours, then crystallizing for 30-180 minutes, and calcining; The template is tetraethylammonium hydroxide, and the molar ratio of the silicon source, aluminum source, template, alkali and water is 1-250:0.05-18:0.3-42:1:5-625, the silicon source is calculated as SiO2, and the aluminum source is calculated as Al2O3.
4. The method according to claim 3, characterized in that In step (1), the molar ratio of the silicon source, aluminum source, template, alkali and water is 1.5-200:0.15-15:0.4-40:1:7-623, wherein the silicon source is calculated as SiO2 and the aluminum source is calculated as Al2O3.
5. The method according to claim 3 or 4, characterized in that In step (2), the crystallization time is 40-150 minutes.
6. The method according to any one of claims 3 to 5, characterized in that In step (2), the raw material mixture is allowed to stand for 1-2 hours.
7. The method according to any one of claims 3 to 6, characterized in that In step (1), the aluminum source is selected from one or more of sodium metaaluminate, aluminum hydroxide and pseudo-boehmite.
8. The method according to any one of claims 3 to 7, characterized in that: In step (1), the silicon source is selected from one or more of silica gel, attapulgite and white carbon black.
9. The method according to any one of claims 3 to 8, characterized in that In step (1), the base is selected from one or more of sodium hydroxide, potassium hydroxide and sodium carbonate.
10. The method according to any one of claims 3 to 9, characterized in that In step (2), the crystallization temperature is 150-200°C, preferably 160-190°C.
11. The method according to any one of claims 3 to 10, characterized in that: In step (2), the calcination conditions include: a calcination temperature of 500-600° C., and a calcination time of 4-6 hours.
12. Beta molecular sieve prepared by the method according to any one of claims 3 to 11.
13. A deoxidation catalyst, characterized in that The deoxygenation catalyst is supported by the Beta molecular sieve according to any one of claims 1, 2 or 12.
14. The deoxidation catalyst according to claim 13, characterized in that The active component of the deoxidation catalyst is one or more of platinum oxide, palladium oxide, silver oxide or gold oxide.
15. The deoxidation catalyst according to claim 13 or 14, characterized in that Based on the total weight of the deoxidation catalyst, the content of the carrier is 97-99.9 weight %, and the content of the active component is 0.1-3 weight %.
Citation Information
Patent Citations
Beta molecular sieve synthesizing method
CN103787355B
Synthesis method of Beta zeolite
CN104229821B